A Study on Purchase Decisions of Celebrity Endorsement on Advertising Campaign in Influencing Consumer – Impact Analysis - D Rajasekar (International Journal of Supply Chain Management, 2018)
Influence plays a important role in the field of advertising by changing the perception attitude of the consumer in information and media explosion.By different celebrities variety of brands is being practiced across the world. The power of celebrities influencing the consumer is being determined by the marketers. Over a period of time celebrity endorsement is in practice. In India the celebrity endorsement business has now turned into evergreen industry. The celebrities in order to increase the sales in the market extend the shares of the marketers who endorsers to increase the purchase decision of consumers. In order to investigate, analyze the relationship of credibility of celebrity endorser and consumer willingness to buy, to find the moderating effect of experience of celebrity are studied in detail. Using standards deviation and regression analysis the participants were asked to answer a questionnaire that corresponded with purchase intentions attitude towards the advertisement and the brand measured against the independent variables, physical attractiveness, source credibility, and celebrity/brand congruency, experience and buying intention by using mean. Using Cronbach alpha test of significance the reliability is being tested. Celebrity endorsements generated higher purchase intentions, positive attitudes toward the advertisement and positive attitudes toward the brand is being found out.